Accounting introductory : Part One - Pasion, Dante S. (Manila, Philippines : Alemar Phoenix Publishers, 1979)
Circumstances and accounting teachers' suggestions have prompted the author to print this revision to his 1959 and 1967 editions.
Chapter 1. Introduction -- 2. The accounting equation -- 3. Debit and credit -- 4. Journalizing and posting -- 5. Simple work sheet and simple financial statements -- 6. Merchandise accounts -- 7. Division of Journal into special books of original entry -- 8. Controlling accounts and division of the ledger -- 9. Negotiable instruments -- 10. Checking account -- 11. Columnar books original entry -- 12. Adjusting, closing and reversing entries.
Keywords: ACCOUNTING